Analisis Hukum Perlindungan Konsumen terhadap Praktik Pinjaman Online Ilegal di Surabaya - Sri Wahyuni; Siti Marwiyah; Subekti . (JOURNAL OF SHARIA ECONOMICS, 2022)
The rapid development of financial technology (fintech) has significantly improved public access to online lending services. However, it has also contributed to the proliferation of illegal online lending platforms, resulting in numerous violations of consumer rights. This study aims to analyze the legal protection afforded to consumers who become victims of illegal online lending practices based on Law Number 8 of 1999 concerning Consumer Protection, Law Number 27 of 2022 concerning Personal Data Protection, Financial Services Authority Regulation Number 22 of 2023 concerning Consumer and Public Protection in the Financial Services Sector, and Law Number 4 of 2023 concerning Financial Sector Development and Strengthening. This research employs a normative legal research method using statutory, conceptual, and case approaches. The data were collected through library research involving primary, secondary, and tertiary legal materials, which were analyzed using descriptive qualitative methods. The findings indicate that Indonesia has established a relatively comprehensive legal framework to protect consumers in the digital financial services sector. Nevertheless, the implementation of legal protection remains ineffective because illegal online lending providers operate outside the licensing and supervisory authority of the Financial Services Authority (Otoritas Jasa Keuangan). The study also identifies several weaknesses, including the absence of a specific legal framework governing financial technology lending, limited jurisdiction over cross-border perpetrators, inadequate inter-agency coordination, insufficient victim recovery mechanisms, and low levels of legal and financial literacy among the public. Therefore, strengthening regulatory harmonization, law enforcement, institutional coordination, and public education is essential to establish a more effective consumer